Iodine status in pregnant women and infants in Finland - Miles Elizabeth A; Vahlberg Tero; Calder Philip C; Houttu Noora; Pajunen Lotta; Koivuniemi Ella; Mokkala Kati; Laitinen Kirsi (Germany, 2022)
Purpose: Iodine insufficiency during pregnancy may adversely influence fetal growth and development. There is a lack of information on iodine status in pregnant women and infants in many countries including Finland. The aim of this study is to determine dietary intake of iodine and the iodine status in a population of Finnish pregnant women and their infants.
Methods: Urine samples were collected from women participating in a mother-child clinical study at early (n = 174) and late pregnancy (n = 186) and at three months of postpartum (n = 197), when infant samples were also collected (n = 123). Urine iodine concentration was measured using inductively coupled plasma mass spectrometry. Cutoffs for iodine insufficiency were < 150 µg/L during pregnancy and < 100 µg/L at postpartum and in infants. Iodine intake was assessed using 3-day food diaries.
Results: Increased risk of insufficiency, based on urinary iodine concentrations, was observed in the groups investigated in this study. Of the women studied, 66% had urinary iodine concentrations indicating insufficient intakes and iodine insufficiency at early pregnancy, 70% at late pregnancy and 59% at three months of postpartum. This was also the case in 29% of the three-month-old infants. Estimation of iodine intake revealed that iodine insufficient women had lower intakes of iodine from the diet, from food supplements and from diet plus supplements than iodine sufficient women in early pregnancy and at three months of post-partum. In late pregnancy, this difference was seen for iodine intake from supplements.
Conclusion: The majority of the women manifested with low urine iodine concentrations both during and after pregnancy. Similarly, one-third of the infants presented with iodine insufficiency. Maternal iodine intake data support these findings. These observations may have implications for optimal child cognitive development.
pport these findings. These observations may have implications for optimal child cognitive development.